Increased dose rate precision in combined α and β counting in the μDose system - a probabilistic approach to data analysis. (June 2020) - Tudyka, Konrad; Bluszcz, Andrzej; Poręba, Grzegorz; Miłosz, Sebastian; Adamiec, Grzegorz; Kolarczyk, Aleksander; Kolb, Thomas; Lomax, Johanna; Fuchs, Markus
Abstract: The μDose system was developed to allow the measurement of environmental levels of natural radioactive isotopes. The system records α and β particles along with four decay pairs arising from successive decays of 214 Bi/ 214 Po, 220 Rn/ 216 Po, 212 Bi/ 212 Po and 219 Rn/ 215 Po. Under the assumption of secular equilibrium, this allows assessing the specific radioactivities of 238 U, 235 U, 232 Th day chains and 40 K. This assessment provides results with uncertainties which are correlated and, thus, require the development of an error estimation methodology which takes this issue into account. In the current work, we present two different approaches for uncertainty propagation based on Monte Carlo and Bayesian methods. Both approaches produce statistically indistinguishable results and allow significantly better dose rate precision than when the correlations are not accounted for. In the given example, the dose rate precision is improved by a factor of two.